MASTICATORY TEST PROCEDURE BASED ON THE USE OF MAN-MADE TEST PATTERNS - Korol, D.M.; Kalashnikov, D.V.; Kindiy, D.D.; Toncheva, K.D.; Zaporozhchenko, I.V. (World of Medicine and Biology, 2018)
Examining the masticatory function as the significant indicator of the patients’ dental health, the authors of the given article enhanced the masticatory test procedure. Since masticatory efficiency was determined in real time mode with the uses of man-made agar masticatory patterns of standardized shape and size. With this aim the recipe of agar gel preparation was improved, and special shadowless photobox with controlled lit area and shooting distance was developed and used. As well as, a particular plugin for automatic computer processing of digital image of the acquired masticatory test fragments was created. The process of chewing man-made patterns involved 95 young volunteers. Аuthors developed and used special plugin for automated masticatory test analysis. So the suggested enhancement of the algorithm of masticatory efficiency determination allows substantial changes in the quality of dental research and practice.
Keywords: masticatory function; masticatory efficiency; masticatory test; masticatory test patterns